CHILD ABUSE IN THE DENTAL SETTING: RECOGNITION, MANAGEMENT, AND PROFESSIONAL RESPONSIBILITY - Baracho, Maria Nazaré Lopes; Martins, Olga Beatriz Lopes; Carneiro-Melo, Callebe; Azevedo, Marielly da Conceição; Mandacaru-Ramos, Danielle; Alcântara, Lívia Fialho; Ramos-Jorge, Maria Letícia (Seven Editora, 2026)
Violence against children constitutes a significant public health and human rights problem, with substantial repercussions for the physical, psychological, and social development of victims. In this context, dentistry plays a relevant role in the early identification of signs of maltreatment, especially due to the high frequency of injuries in the orofacial region. This study aimed to map and synthesize the scientific evidence on the role of dentists in the identification, management, referral, and prevention of child abuse. A literature review was conducted in the PubMed/MEDLINE, Scopus, Web of Science, Science Direct, BVS (LILACS and SciELO), and Google Scholar databases, using descriptors related to child abuse and dentistry. Studies on children up to 12 years of age treated in dental settings were included, without restriction of language or publication period. Initially, 2,595 records were identified; after removing duplicates and applying eligibility criteria, 273 studies comprised the final sample. The results indicate a growth in scientific production on the subject, with descriptive studies focused on identifying clinical signs and professional perception predominating. However, gaps persist related to academic training, diagnostic uncertainty, and underreporting of cases. It is concluded that dentists play a strategic role in the child protection network, and it is necessary to strengthen professional training, intersectoral integration, and the development of evidence-based protocols and strategies to improve the identification and management of child abuse.